Front-End Development of Amikom Purwokerto University Finance Website Using Bootstrap - Huberta, Bima; Rakhmawati, Desty; Wijaya, Anugerah Bagus (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
At Universitas Amikom Purwokerto, the Institute for Research and Community Service (LPPM) faces significant challenges in financial data processing. Currently, financial data is managed using Microsoft Excel, and there is no system in place to properly manage and store this data. This lack of an efficient system hinders effective financial management and data handling. To address these issues, the proposed solution is to develop a website for financial management that supports the tri dharma of higher education. Effective web application development necessitates adherence to standard front-end framework models. Therefore, this study focuses on creating a front-end for the LPPM financial website using Bootstrap, following the waterfall method due to its sequential, structured, and reliable properties. The result of this study is a website-based LPPM financial application front-end. Based on test results, the front-end of this website achieved an SUS (System Usability Scale) score of 80.5, which falls into grade B. This indicates that the application is expected to facilitate the process of managing financial data and enhance user interaction with the system, effectively resolving the identified issues. This research was successful because it had created a front-end system in accordance with the needs that had been complained about by the university.